Citybildung im späten 19. und frühen 20. Jahrhundert: Das Beispiel Berlin. - Koser, David (Deutsches Institut für Urbanistik, 2019)
In the period between the foundation of the German Reich in 1871 and the Second World War the central areas of Berlin turned into a modern city centre. In the German language, this process is described as "Citybildung" (city development). The article covers the course of this development in the core area of the city centre, the baroque districts Dorotheenstadt and Friedrichstadt. Parameters of the examination are land use, building activity, parcelling and the resident population. The primary sources for the examination were historical directories and building files. The investigation reveals that the districts Dorotheenstadt and Friedrichstadt experienced first a phase of upgrading after the foundation of the German Reich. Despite the growing importance of the tertiary sector both quarters continued to be favourite residential areas. The actual development of the city centre started in the 1890s, leading to the exodus of local residents and the rapid spread of the tertiary sector. The first world war set an abrupt end to this development. Whereas the functional structures in the area remained almost unchanged during the 1920s, the tertiary sector was shrinking for the first time in the 1930s.
Keywords: Großstadt; Hauptstadt; Industrialisierung; Strukturwandel; Nutzungswandel; Stadtstruktur; Stadtentwicklung; Citybildung; Stadtgeschichte; Stadtbaugeschichte